PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kota Tanjungpinan - Siahaan, Chris Aditya; Savitri, Enni; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to examine the effect of Budgetary Participation and Budget Goal Clarity on the Managerial Performance in the Special District of Tanjungpinang with Job Satisfaction and Commitment Organizational as Moderating Variable at SKPD Tanjungpinang City. The data in this study is the primary data. The population in this study were the local government officials who worked at SKPD Tanjungpinang city. The sampling method used in this study census method. The sample used in this study were 80 respondens. Based on the data collected and testing has been done on the problem by using regression analysis method, it can be conclude: 1) the effect of budgetary participation having an effect on managerial performance, 2) the effect budget goal clarity having an effect on managerial performance, 3) job satisfaction moderate the relationship of budgetary participation towards managerial performance, 4) commitment organizational moderate the relationship of budgetary participation towards managerial performance, 5) job satisfaction moderate the relationship of budget goal clarity towards managerial performance, 6) commitment organizational moderate the relationship of budgetary goal clarity towards managerial performance. All of independent and moderating variable influencing the dependent of 73,8%, while the remaining 26,2% is influenced by other variable that are not observed in this study.Keywords : Budgetary, Performance and Commitment.